Analisis Kualitas Pelayanan TerhadapKepuasan Pelanggan Properti DiPt Restu Adi Karanganyar - Islammiah, Shalis Nurul, Dr. Anton Agus Setyawan, SE.,M.Si (2017)
This study aimed to analyze the quality of service to customer satisfaction PT Restu Adi property in Karanganyar. This study is a qualitative peneletian, methods of data used is primary data in the can by distributing questionnaires as many as 100 customers of PT Restu Adi. The sampling technique used isidental sampling. The analytical tool used in this research is multiple linear regression, using SPSS. The results showed that a significant berpengerahuh service quality to customer satisfaction, and customer loyalty has no significant effect on customer satisfaction